Teaching Note—A Call for Social Work Education Modification: Moving Toward a Model of Interprofessional Education. (2nd July 2020) - Deichen Hansen, Megan; Holland, Margaret M.; Munn, Jean
ABSTRACT: Interprofessional health-care models have been largely recognized as a critical component of effective and efficient health-care provision. While many health professions have established methods of exposing their students to interprofessional health models, social work has been slow to join in on this educational movement. In an effort to provide their students with increasingly important educational opportunities, one Southeastern university implemented the Geriatric Workforce Enhancement Program (GWEP), which promotes interprofessional collaboration within schools of nursing, medicine, and social work. This teaching note provides a detailed account of how one school of social work used GWEP to enhance interprofessional student learning. Preliminary findings illustrate the importance of integrating cutting-edge interprofessional education opportunities into social work curriculum.